Heavy metal in different size fractions of household dust collected from rural residential area of Simpang Renggam, Johor - Tay, Joo Hui; Siti Aqilah, Azmi; Mohd Iffat Iqbal, Zul Kornain (The Malaysian Analytical Sciences Society, 2021)
A study investigating the levels of selected heavy metals in household dust from a rural residential area was carried out. Household dust was collected from seven residential homes within the area of Simpang Renggam, Johor. All samples were sieved through a 200 μm sieve, in which two dust samples with sufficient masses (sample A and B) were further separated into four discrete fractions (<63 μm, 63-75 μm, 75-150 μm, and 150-200 μm) before analysis. Dust samples were acid digested and analyzed for the content of Al, Cr, Mn, Ni, Zn, Cu, Cd, Ba, Pb, Mg, and Fe using inductively coupled plasma - mass spectrometer (ICP-MS). Results showed that the Fe and Al were among the most abundant elements in bulk dust samples (mean concentration of 8500 mg/kg and 5100 mg/kg, respectively), and their concentrations increased with decreasing particle size. Mean concentrations of other elements ranged between 0.027 mg/kg to 2310 mg/kg. For Mn, Mg, Cu, and Zn, higher levels were measured in coarser particle size. Health risk estimation indicated that Hazard Quotient (HQ) and Hazard Index (HI) values were below than 1, representing no noncarcinogenic risk to the residents via ingestion, inhalation, and dermal absorption.